Echocardiographic and pathomorphological features in fetuses with ductal‐dependent congenital heart diseases. Issue 9 (7th August 2019) - Jiang, Huan; Tang, Qi; Jiang, Yan; Li, Ningshan; Tang, Xuefeng; Xia, Hongmei
Abstract: Objective: To individually analyze echocardiographic features in fetuses with ductal‐dependent congenital heart diseases (DDCHD) and to verify the anatomical characteristics corresponding to the echocardiogram scan views. Background: Ductal‐dependent congenital heart diseases depends on the ductus arteriosus (DA) remaining open to maintain suitable pulmonary or systemic circulation after birth. An accurate diagnosis using prenatal echocardiography has important clinical significance in evaluating disease prognosis and ensuring timely treatment. Methods: Fetuses were followed in the prenatal and postpartum periods via echocardiography. The results of postpartum echocardiography or autopsy specimens were compared with the prenatal echocardiography findings. Results: One hundred and eight fetuses displayed various types of DDCHD including 66 fetuses with ductal‐dependent pulmonary circulation, and 42 fetuses with ductal‐dependent systemic circulation. Prenatal echocardiography revealed the typical characteristics of no forward flow signal from right ventricular outflow tract to the pulmonary trunk proximally and a reverse flow in the DA in most fetuses for ductal‐dependent pulmonary circulation, a reverse flow in the transverse aortic arch for aorta atresia, and a loss of continuity between aortic arch and descending aorta for interruption of the aortic arch (IAA). All 108 fetuses displayed various types of complex CHD, including right ventricular dysplasia with pulmonary atresia (PA), severe Ebstein anomaly, double outlet right ventricle with PA, tetralogy of fallot with PA, single ventricle with PA or aorta atresia, hypoplastic left heart syndrome, and IAA. Conclusions: The identification of reverse flow in the aortic arch or DA aids in the subsequent accurate diagnosis of DDCHD associated with complex malformation of the heart.